A history of asthma may be associated with grandparents’ exposures to stress and cigarette smoking - Golding, Jean; Tunstall, Holly; Gregory, Steve; Granell, Raquel; Dodd, James W.; Iles-Caven, Yasmin; Watkins, Sarah; Suderman, Matthew (Frontiers in Toxicology, 2023)
Introduction: Within human epidemiological studies, associations have been demonstrated between grandparental exposures during childhood and grandchildren’s outcomes. A few studies have assessed whether asthma has ancestral associations with exposure to cigarette smoking, but results have been mixed so far. Material and methods: In this study we used four generations: (F0 great-grandparents, F1 grandparents, F2 parents, F3 study children) of the Avon Longitudinal Study of Parents and Children (ALSPAC) to determine whether there is evidence of associations between asthma in generations F2 or F3 and exposures to severe trauma in childhood and/or active cigarette smoking during the adolescence of grandmothers and grandfathers in generations F0 and F1 respectively, or of a history of a F0 or F1 grandmother smoking during pregnancy. Results: We have shown that: a) stress exemplified by the death of a F1 grandparent’s parent during the grandparents’ childhood was associated with increased risk of asthma in generation F3, especially if the grandparent involved was the paternal grandmother; b) if the grandparents of generations F0 or F1 smoked during adolescence (i.e. < 17 years), their grandchildren in generations F2 and F3 were more likely to have a history of asthma; c) paternal F1 grandmother’s smoking in pregnancy was associated with her F3 grandchild’s asthma at age 7; d) There were differences between the results for the grandsons and granddaughters of the paternal grandmother with exposure to smoking in adolescence and with smoking in pregnancy. e) The addition of all of the individual exposure variables to the different analyses often provided a considerable increase in goodness of fit compared with only adding demographic factors associated with asthma at P < 0.10 such as social class; this was particularly true when all four exposure variables were combined in one model, suggesting possible synergistic effects between them. Discussion: We have shown associations between all four types of exposure to the grandparents to be associated with asthma in the grandchildren, such that the results both depended on whether the male or female line was involved, and the sex of the grandchildren. It was notable that the paternal grandmother was particularly involved in many of the associations. We emphasize that these are exploratory analyses, that asthma diagnostic criteria likely changed over time and may not be consistent between generations, and that the results should be tested in other cohorts.